2018
DOI: 10.3174/ajnr.a5669
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Perfusion Is Perturbed by Preterm Birth and Brain Injury

Abstract: We report early disturbances in global and regional CBF in preterm infants following brain injury. Regional cerebral perfusion alterations were evident in the thalamus and pons, suggesting regional vulnerability of the developing cerebro-cerebellar circuitry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Measurement of exact arterial transit delay in newborns may be warranted in future studies to confirm optimal postlabeling delay. Our quantified global CBF measurements in preterm infants are largely in agreement with previous preterm ASL studies (6)(7)(8)(9)(12)(13)(14)(15). Our measurements are most comparable to those in the studies by De Vis et al (7)(8)(9), in which T1 b was measured in each infant, similar to our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Measurement of exact arterial transit delay in newborns may be warranted in future studies to confirm optimal postlabeling delay. Our quantified global CBF measurements in preterm infants are largely in agreement with previous preterm ASL studies (6)(7)(8)(9)(12)(13)(14)(15). Our measurements are most comparable to those in the studies by De Vis et al (7)(8)(9), in which T1 b was measured in each infant, similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…We report a significant association between CBF and IVH in preterm infants. Previous studies also demonstrated associations between brain injury and low ASL CBF (12)(13)(14) or low oxygen delivery based on results of near-infrared spectroscopy (32,33). Particularly, one study showed that oxygen delivery in the preterm brain was associated with IVH but not parenchymal injury (32).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, studies beyond early adulthood are limited, with most studies employing a single method approach. Further, to our knowledge, GM perfusion has not been examined in this population beyond infancy despite preliminary data showing that preterm birth may be associated with both increased and decreased cerebral perfusion (Mahdi et al, 2018). Perfusion dysfunction may be associated with structural alterations, and has even been shown to precede structural loss in some scenarios (ChĂ©telat et al, 2007; Gonzalez-Redondo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that compared with healthy mice, the apoptosis of hippocampal CA1 and cortical neurons in the brain injury model of preterm mice increased significantly, and the level of Bax protein increased significantly and the level of Bcl-2 protein decreased significantly. It shows that obvious damage occurred in the brain tissue of preterm mice [ 25 ]. EPO can reduce neuronal apoptosis and increase the ratio of Bcl-2/Bax in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%